The prevalence, comorbidities, influencing factors, and identifying factors of non-obese fatty liver disease - Gao, Ning; Deng, Jiang; Wang, Jinhai; Zhou, Zhihua; Yao, Cong; Zhou, Mimi; Xing, Xin; Wang, Qian; Lu, Xiaolan; Shi, Haitao (Frontiers in Medicine, 2022)
Method: Firstly, to screen data obtained from the physical examinations of individuals conducted in the Second Affiliated Hospital of Xi'an Jiaotong University in 2021 involving comprehensive data inclusive of abdominal ultrasonography, body mass index, age, and gender to analyze the prevalence of fatty liver disease and non-obese fatty liver disease. Secondly, to screen the non-obese subjects who have data for triglycerides, fasting blood glucose, and so on, to analyze the complications, influence, and predictive factors of non-obese fatty liver disease. Results: The prevalence of fatty liver was 27.8% (18416/66221), including 33.9% (11921/35131) in males and 20.9% (6495/31090) in females, showing that the prevalence was significantly higher in males than in females (P<0.001). There were 40673 non-obese subjects screened in total, and the prevalence of non-obese fatty liver was 13.4% (5307/40673). The prevalence of non-obese fatty liver in males was 13.3% (2208/16572) and 12.9% (3099/24101) in females, the difference was not statistically significant (P=0.17). The serum triglyceride level was elevated in 54.2% of subjects with non-obese fatty liver disease, and this was the most common abnormal metabolic index accompanying the disease. Logistic regression analysis showed that gender, age, blood pressure, alanine aminotransferase, aspartate aminotransferase, fasting blood glucose, triglycerides, total cholesterol, and serum uric acid were independent risk factors for non-obese fatty liver (P<0. 001). For triglycerides, the area under the receiver operating characteristic curve in predicting non-obese fatty liver was the greatest (0.806). Conclusions: The prevalence of fatty liver and non-obese fatty liver among the physical examination of individuals was high, triglycerides is likely to be useful for the extensive screening of non-obese fatty liver disease.